Quadratic stochastic operators on simplex - Saburov, Mansoor (2015)
In this talk, we first review some basic results of square stochastic matrices concerning the convergence of power of square stochastic matrix. We also discuss a linear operator associated with a square stochastic matrix. This gives an advantage to interpret all results by means of the language of dynamical system. In the second part of this talk, we discuss on a cubic stochastic matrix.